IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH THROUGH SEMANTIC MAPPING TECHNIQUE - Ridho Sari C. Sitanggang; Siti Aisah Ginting (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2012)
ABSTRACT This study attempts to improve students’ achievement in writing descriptive paragraph through Semantic Mapping Technique. This study was conducted by using classroom action research. The subject of the research was class (IX/A) SMP St. Petrus Medan that consisted of (30) students. The research was conducted in two cycles. The instruments of collecting data were quantitative data (Writing Test) and Qualitative data (diary notes, observation sheet, interview and questionnaire sheet). Based on the data analyzing, it is found that students’ writing descriptive paragraph has improved from the orientation test to the test I and test II of the first and second cycle. It means that there is improvement in students’ writing descriptive paragraph affected by semantic mapping. It can be seen from the improvement of the students’ mean score for orientation test (52,5); test cycle I (62,04); and test cycle II (71,25). The students’ score continuously improved in each test. Therefore, it can be concluded that Semantic Mapping Technique can improve students’ achievement in writing descriptive paragraph.   Keywords: students’ achievement, writing, genre, semantic mapping technique